Hill Cipher with r-Circulant Matrices - Dalkılıç, Şeyda; Kepekçi, Ahmet Eren; Baştürk, Muhammed Zekeriya (Journal of Engineering Technology and Applied Sciences, 2025)
The Hill cipher, a historic symmetric encryption method, has limitations in contemporary cryptography. This study explores enhancing its security by incorporating r-circulant matrices. Existing literature employs circulant matrices within the Hill cipher. In this study we propose a novel encryption algorithm that employs r-circulant matrices with the objective of increasing the algorithm's complexity and resistance to cryptanalysis. The developed algorithm demonstrably achieves a more secure and intricate encryption process which is supported by comparisons and numerical data. Once the algorithm has been identified, it is translated into a computer code and implemented as a program in the Python software language.